The Impact of the Global Financial Crisis on Banking Globalization - Claessens, Stijn (IMF Working Papers; Working Paper ;, 2014)
Although cross-border bank lending has fallen sharply since the crisis, extending our bank ownership database from 1995-2009 up to 2013 shows only limited retrenchment in foreign bank presence. While banks from OECD countries reduced their foreign presence (but still represent 89% of foreign bank assets), those from emerging markets and developing countries expanded abroad and doubled their presence. Especially advanced countries hit by a systemic crisis reduced their presence abroad, with far flung and relatively small investments more likely to be sold. Poorer and slower growing countries host fewer banks today, while large investments less likely expanded. Conversely, faster host countries' growth and closeness to potential investors meant more entry. Lending by foreign banks locally grew more than cross-border bank claims did for the same home-host country combination, and each was driven by different factors. Altogether, our evidence shows that global banking is not becoming more fragmented, but rather is going through some important structural transformations with a greater variety of players and a more regional focus.